1999
DOI: 10.1023/a:1006790912877
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Interactions of tumor cells with the endothelium and tissue stroma are considered to be critical steps in metastasis formation and progression of cancer. To identify cellular receptors that mediate the binding of tumor cells to endothelium, a murine T cell lymphoma-derived expression library was screened for adhesion-inducing cDNA clones. We identified a novel cell adhesion-promoting molecule, termed ARM-1 (adhesion regulating molecule-1), which is homologous to a human Mr 110,000 tumor-associated antigen. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…In ADRM1 knock-out mice, the most notable phenotype is a defect in oogenesis, suggesting that ADRM1 normally plays a critical role in ovarian development [7]. The role ADRM1 plays in ovarian cancer is unknown but it has been shown to be upregulated in metastatic tumor cells, and its overexpression increased the propensity of cells to engage in cell-cell interactions [2,8]. A study of commonly overexpressed genes in solid tumors by microarray analysis shows that ADRM1 is consistently over-expressed in multiple tumor types, including lung adenocarcinoma, lung squamous cell carcinoma, bladder, colon, liver, kidney, and stomach cancer in addition to ovarian cancer [9], suggesting that this gene may be a potential target in many tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…In ADRM1 knock-out mice, the most notable phenotype is a defect in oogenesis, suggesting that ADRM1 normally plays a critical role in ovarian development [7]. The role ADRM1 plays in ovarian cancer is unknown but it has been shown to be upregulated in metastatic tumor cells, and its overexpression increased the propensity of cells to engage in cell-cell interactions [2,8]. A study of commonly overexpressed genes in solid tumors by microarray analysis shows that ADRM1 is consistently over-expressed in multiple tumor types, including lung adenocarcinoma, lung squamous cell carcinoma, bladder, colon, liver, kidney, and stomach cancer in addition to ovarian cancer [9], suggesting that this gene may be a potential target in many tumor types.…”
Section: Introductionmentioning
confidence: 99%
“…ADRM1 was originally identified as ADhesion Regulating Molecule-1 in metastatic tumor cells [ 28 ]. Several observations have driven interest in RPN13 ’s role in cancer biology; 1) early studies suggested that ADRM1 transcript levels commonly upregulated in diverse tumor types [ 29 ], 2) ADRM1 was identified as a recurrent amplification target in ovarian cancer [ 30 32 ], colorectal carcinoma [ 33 , 34 ], gastric cancer [ 35 , 36 ], 3) knockdown of ADRM1 transcripts suppressed proliferation, growth in soft agar and migration of diverse cancer lines but not normal cells [ 31 , 34 – 39 ], 4) over-expression of RPN13 via ectopic expression of ADRM1 enhanced proliferation [ 32 , 35 ], 5) ADRM1 -encoded RPN13 is required for cell cycle progression [ 40 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Rpn13 protein, previously termed adhesion-regulating protein 1 or GP110, has been identified as a tumor-associated gene product [1], [2], [3], [4], [5], [6], and more recently as an amplification target in ovarian cancer [7]. Initially, Rpn13 was suggested to regulate cell adhesion as a membrane-associated protein [2], but further examination revealed that it is primarily a cytosolic protein associated with proteasomes [8].…”
Section: Introductionmentioning
confidence: 99%
“…Initially, Rpn13 was suggested to regulate cell adhesion as a membrane-associated protein [2], but further examination revealed that it is primarily a cytosolic protein associated with proteasomes [8]. Proteasomes are central molecular complexes of the non-lysosomal, ubiquitin-ATP-dependent protein degradation pathway.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation